Traffic-load fragility models for prestressed concrete girder decks of existing Italian highway bridges. (15th December 2021) - Miluccio, Giacomo; Losanno, Daniele; Parisi, Fulvio; Cosenza, Edoardo
Highlights: Statistical analysis of existing Italian prestressed concrete girder bridge decks. Computational procedure based on uncertainty modelling, ultimate capacity models and deck analysis. Tornado diagrams to quantify the sensitivity of structural performance to multiple variables. Probabilistic structural analysis of bridge decks using Monte Carlo simulation. Traffic-load fragility models for large-scale risk assessment of existing highway bridges. Abstract: Even if previous studies investigated seismic fragility of existing bridges, some recent collapse cases set the need to investigate their vulnerability under gravity loads. In this study, the class of simply supported, beam-type, prestressed concrete bridges built between 1970 and 1980 was considered to carry out a fragility analysis of the most recurrent type of Italian bridges to traffic loads. Based on the literature and new data collected by the authors from real bridges, geometric, material and load variables were defined through probability distributions and regression models. Then, a code-based capacity modelling of bridge decks was carried out, followed by the implementation of a simplified deck analysis method that allows extensive simulations. In a first step, a sensitivity analysis was performed to identify the random variables that mostly affect the structural response, to be taken into account in the fragility analysis for the ultimate limit state. Then, a fragility analysis was carried through a fully automatic procedure implemented in MATLAB. The main output consists of fragility models that might be used by engineers, roadway management companies and decision-makers in large-scale risk assessments of existing highway bridges under code-based traffic loads, as a basis for prioritization of more refined performance evaluations and structural retrofitting programmes.